Biomarkers for recurrent pressure injury risk in persons with spinal cord injury. (2nd September 2020) - Schwartz, Katie; Henzel, M. Kristi; Ann Richmond, Mary; Zindle, Jennifer K.; Seton, Jacinta M.; Lemmer, David P.; Alvarado, Nannette; Bogie, Kath M.
Abstract : Objective: To investigate potential linkages between pressure injury (PrI) recurrence following spinal cord injury (SCI) and muscle-based and circulatory biomarkers, specifically fatty metabolites and inflammatory cytokines. Design: Observational study. Setting: Tertiary Care Center. Participants: 30 individuals with complete or incomplete SCI. Study participants either had never developed a PrI (Group I) or had a history of recurrent PrI (Group II). Interventions: Not applicable. Outcome Measures: Gluteal muscle histology, immunohistochemistry, muscle-based and circulatory fatty metabolites and inflammatory cytokines. Results: Gluteal intramuscular adipose tissue (IMAT) was greater than 15% in most Group II (83%) individuals. Muscle tissue histology confirmed intramuscular structural differences. Fatty acid binding protein 4 (FABP4) and fatty acid binding protein 3 (FABP3) were reliably detected in muscle and blood and significantly correlated with IMAT (P < 0.001). FABP4 was significantly higher in Group II muscle and blood (P < 0.05). FABP3 was significantly higher in Group I muscle (P < 0.05). Circulatory FABP3 levels were lower for Group I. Inflammatory biomarkers were more reliably detected in blood. Colony-Stimulating Factor-1 was slightly higher in Group II muscle. Circulatory interleukin-13 was significantly higher (P < 0.01) in Group I. Vascular endothelial growth factor (VEGF-A) was significantly increased (P < 0.05) in Group I muscle and blood. Conclusion: Identifying individuals with SCI at highest risk for recurrent PrI may impact patient management. IMAT content evaluation illustrates that muscle quality is a key biomarker. Low circulatory inflammatory biomarker expression potentially limits clinical significance for between group differences. Circulatory levels of FABP4 hold great potential as a recurrent PrI risk biomarker.